Continuous frame in Hilbert spaces - Rahimi, A.; Najati, A.; Dehghan, Y. N. (Methods of Functional Analysis and Topology, 2006)
In this paper we introduce a mean of a continuous frame which is a generalization of discrete frames. Since a discrete frame is a special case of these frames, we expect that some of the results that occur in the frame theory will be generalized to these frames. For such a generalization, after giving some basic results and theorems about these frames, we discuss the following: dual to these frames, perturbation of continuous frames and robustness of these frames to an erasure of some elements.